Kepemimpinan Profetik dalam Pendidikan Islam - Lutfi Faishol (Eduprof : Islamic Education Journal, 2020)
As a Muslim who has guidelines in the life, namely the Qur’an and Hadis , the Qur'an and Hadis should be used as an example in living this life. Included in the issue of leadership, So each leader shoud rest on the concept that is relevant to Islamic teachings. This thing that should be an example in leading is the leadership of the Prophet (prophetic). The success of leadership that has been proven by the Prophet Muhammad is as a leader, he is the most successful and influential person of all time. In Islam, leadership is believed to have a value that is typical of mere subordinate participation and achievement of organizational goals. There are transcendental values that are struggeled in prophetic leadership in any organization. The concept of leadership in Islam is not only horizontal-formal towards fellow humans, but also is vertical-moral that we have responsibility to the God on the last day. These values become the basis for conducting leadership activities. Where prophetic leadership is a leadership that bases the personality of the Prophet in carrying out his leadership. Because prophetic leadership in the Qur'an has been mentioned and has been exemplified by the Prophet. As a leader in carrying out prophetic leadership, they need to know and emulate the characteristics of the Prophet (peace and blessings of Allah be upon him) that can lead themselves, giving an example, able to communicate well, close to the people that they lead, always consulting, and giving motivation and praise. Prophetic leadership is manifested as a position of leader who take the responsibility for achieving the goals and expectations of the agency / organization through its leadership activities. Abstrak Sebagai seorang muslim yang memiliki pedoman dalam hidupnya yakni al Quran dan Hadits, maka sepantasnya al Quran dan Hadits dijadikan sebagai teladan dalam menjalani hidup ini. Termasuk dalam masalah kepemimpinan, setiap pemimpin berpijak pada konsep kepemimpinan yang relevan dengan ajaran Islam. Hal ini yang sebaiknya menjadi teladan dalam memimpin adalah kepemimpinan Nabi (propetic). Keberhasilan kepemimpinan yang telah dibuktikan oleh Nabi Muhammad saw adalah selaku seorang pemimpin, Beliau adalah orang yang paling berhasil dan berpengaruh sepanjang masa. Dalam Islam, kepemimpinan diyakini mempunyai nilai yang khas dari sekedar kepengikutan bawahan dan pencapaian tujuan organisasi. Ada nilai-nilai transendental yang diperjuangkan dalam kepemimpinan profetik dalam organisasi apapun. Konsep kepemimpinan dalam Islam tidak hanya bersifat horizontal-formal terhadap sesama manusia, akan tetapi bersifat vertical-moral yakni adanya sebuah tanggungjawab dihadapan Allah di hari ahir kelak. Nilai-nilai tersebut menjadi pijakan dalam melakukan aktifitas kepemimpinan. Dimana kepemimpinan profetik merupakan kepemimpinan yang melandaskan kepribadian dari Rasulullah saw dalam menjalankan kepemimpinannya. Karena kepemimpinan profetik dalam al quran telah disinggunng serta sudah dicontohkan oleh Rasulullah saw. Sebagai seorang pemimpin dalam menjalankan kepemimpinan profetik, mereka perlu mengetahui dan meneladani sifat-sifat Rasulullah saw yakni dapat memimpin diri sendiri, memberikan teladan, dapat berkomunikasi dengan baik, dekat dengan orang-orang yang dipimpinnya, selalu bermusyawarah, serta memberikan motivasi dan pujian. Kepemimpinan profetik diwujudkan sebagai posisi/jabatan leader yang memikul tanggung jawab untuk mencapai tujuan dan harapan dari instansi/organisasi melalui aktivitas-aktivitas kepemimpinannya.